A Rapid Inoculation Method for Infection of Ganoderma in Oil Palm - Purnamasari, Maria Indah; Agustina, Delia; Prihatna, Cahya; Suwanto, Antonius (International Journal of Oil Palm, 2018)
Basal stem rot (BSR) is a major disease of oil palm plantation caused by pathogenic fungus Ganoderma boninense. To overcome the disease, development of resistant or tolerantoil palms is crucial for susta inable production of palm oil. Thus a reliable and rapid method to assess resistance of oil palm to BSR is important. Here we report an inoculation technique designated as mycelium inoculation technique. This method is faster and simpler compared to the traditional technique using rubber wood block. The technique that we developed results in consistency of infection and disease can be evaluated as early as two weeks after inoculation with G. boninense. Furthermore, this method is also able to di?erentially assess resistant and susceptible palm seedlings to BSR. The results show that this new inoculation technique can be used as a routine method to infect oil palm seedlings and can be utilised for development of resistant cultivar of oil palm to G. boninense.